Peran Public Relations Dalam Perusahaan Untuk Memahami Lingkungan - Pratiwi, Restu Meiditya; Pranawukir, Iswahyu (Prisani Cendekia Institute, 2024)
Public relations and communications management covers wide range of ideas such as media relations, public affairs, community affairs, product publicity, events management, crisis management, lobbing, investor relations etc. The perception of public management and its roles are changing. The enterprises face the challenges such as fast technological changes, developing of international relations and growing global competition. What is also changing is the nature and tools of communication, what influences the public relations management. Public relations may be a strategic resource which, when appropriately managed, may contribute to effective realization of the strategy of an enterprise. Modern public relations help to understand the environment of an organization and maintain the relations with groups significant to achieving the strategic goals of an enterprise. What is also important issue for modern public relations is an ethical approach to business, social, and environmental responsibility.